Biomechanical Analysis of Coracoid Stability After Coracoplasty: How Low Can You Go?. Issue 2 (25th February 2022) - Heilmann, Lukas F.; Sussiek, Julia; Raschke, Michael J.; Langer, Martin F.; Frank, Andre; Wermers, Jens; Michel, Philipp A.; Dyrna, Felix; Schliemann, Benedikt; Katthagen, J. Christoph
Background: Arthroscopic coracoplasty is a procedure for patients affected by subcoracoid impingement. To date, there is no consensus on how much of the coracoid can be resected with an arthroscopic burr without compromising its stability. Purpose: To determine the maximum amount of the coracoid that can be resected during arthroscopic coracoplasty without leading to coracoid fracture or avulsion of the conjoint tendon during simulated activities of daily living (ADLs). Study Design: Controlled laboratory study. Methods: A biomechanical cadaveric study was performed with 24 shoulders (15 male, 9 female; mean age, 81 ± 7.9 years). Specimens were randomized into 3 treatment groups: group A (native coracoid), group B (3-mm coracoplasty), and group C (5-mm coracoplasty). Coracoid anatomic measurements were documented before and after coracoplasty. The scapula was potted, and a traction force was applied through the conjoint tendon. The stiffness and load to failure (LTF) were determined for each specimen. Results: The mean coracoid thicknesses in groups A through C were 7.2, 7.7, and 7.8 mm, respectively, and the mean LTFs were 428 ± 127, 284 ± 77, and 159 ± 87 N, respectively. Compared with specimens in group A, a significantly lower LTF was seen in specimens in group B ( P = .022) and group C ( P < .001). Postoperatively, coracoids with a thickness ≥4 mm were able to withstand ADLs. Conclusion: While even a 3-mm coracoplasty caused significant weakening of the coracoid, the individual failure loads were higher than those of the predicted ADLs. A critical value of 4 mm of coracoid thickness should be preserved to ensure the stability of the coracoid process. Clinical Relevance: In correspondence with the findings of this study, careful preoperative planning should be used to measure the maximum reasonable amount of coracoplasty to be performed. A postoperative coracoid thickness of 4 mm should remain.